2016
DOI: 10.18632/oncotarget.12785
|View full text |Cite
|
Sign up to set email alerts
|

Application of intensity-modulated radiotherapy in unresectable poorly differentiated thyroid carcinoma

Abstract: Poorly differentiated thyroid carcinoma (PDTC) is a rare and aggressive malignancy with high rates of invasion and distant metastasis. This study was to explore the ability of intensity-modulated radiotherapy (IMRT) combined with chemotherapy to manage unresectable PDTC. Between February 2011 and April 2012, 5 patients with unresectable PDTC were treated by IMRT at our institution and were included in this analysis. The median radiotherapy dose to the gross tumor volume (GTV) was 66 Gy/33 fractions/6.4 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In the majority of studies in our review, the extent of the poorly differentiated area was not reported, and a PDTC definition was decided to address this component. A large number of patients with PDTC reviewed herein presented with locally advanced disease (T3 or T4, extrathyroidal extension, and nodal involvement) [ 40 , 44 , 46 , 47 , 49 , 50 , 51 , 54 , 55 , 57 , 58 , 60 , 61 , 62 , 64 , 67 , 68 , 69 , 70 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 90 , 91 , 92 , 94 , 97 , 98 , 99 , 100 , 101 , 102 , 107 , 108 , 109 , 111 , 112 , 113 , 114 , 115 , 116 ,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of studies in our review, the extent of the poorly differentiated area was not reported, and a PDTC definition was decided to address this component. A large number of patients with PDTC reviewed herein presented with locally advanced disease (T3 or T4, extrathyroidal extension, and nodal involvement) [ 40 , 44 , 46 , 47 , 49 , 50 , 51 , 54 , 55 , 57 , 58 , 60 , 61 , 62 , 64 , 67 , 68 , 69 , 70 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 90 , 91 , 92 , 94 , 97 , 98 , 99 , 100 , 101 , 102 , 107 , 108 , 109 , 111 , 112 , 113 , 114 , 115 , 116 ,…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no effective targeted chemotherapeutic regime for PDTC. Cisplatin/doxorubicin and carboplatin/paclitaxel are similar combinations that are used to modulate disease progression, and likewise, only a few of the revised studies used these schemes for select patients [ 42 , 57 , 60 , 78 , 97 , 114 , 119 ].…”
Section: Discussionmentioning
confidence: 99%